A Systematic Review of Architectural Atmosphere That Fosters Mindfulness Constructs - Chaniporn Thampanichwat; Limpasilp Sirisakdi; Sippakorn Petsirasan; Duangkamon Wutisun; Sathirat Singkham; Tarid Wongvorachan; Prima Phaibulputhipong; Suphat Bunyarittikit; Rungroj Wongmahasiri (Buildings, 2025)
This study explores how architectural atmosphere can foster mindfulness constructs in response to the growing mental health crisis. Mindfulness, known for improving mental health, reducing stress, and enhancing overall well-being, is increasingly recognized as a potential solution to mental health challenges. However, research on how architectural atmosphere supports mindfulness is limited. This study systematically reviews architectural atmosphere features that promote mindfulness constructs, which includes awareness, openness, attention, focus, connection, and calmness. A literature review was conducted using the Scopus database, following PRISMA guidelines for transparency. Fifty-three articles were selected, focusing on mindfulness features in architectural atmosphere: awareness (4), openness (1), attention (28), focus (5), and connection (15). No studies were found on architectural atmosphere fostering calmness. The findings suggest that architectural atmosphere plays a significant role in supporting mindfulness, but further empirical studies are needed to validate these results in real-world contexts.